Why clean sport is more than just drug-free - Petróczi, A. (Nature, 2021)
The world of sport is replete with rhetoric involving the word `clean`. Whether in the mission statements of organizations such as UK Anti-Doping or in the names of groups such as the US non-profit organization the Partnership for Clean Competition, clean is used as a label of integrity, authenticity and fairness. Yet, despite the pervasiveness of the term, it is not always clear what clean sport really is. Often the definition revolves around the use of prohibited performance-enhancing drugs or methods. Performance enhancement is encouraged in sport, provided it is achieved through legitimate means. When strategies for boosting performance employ substances or methods specifically outlawed by a governing body, such as the World Anti-Doping Agency (WADA), the practices become doping.